Efficacy of Intermittent Theta-Burst Stimulation and Transcranial Direct Current Stimulation in Treatment of Post-Stroke Cognitive Impairment - Minmin Chu; Youmei Zhang; Jianer Chen; Weihai Chen; Zhenmei Hong; Yue Zhang; Hong Yu; Feilan Zhang; Xiancong Ye; Jingjing Li; Yun Yang (Journal of Integrative Neuroscience, 2022)
Background: The efficacy of intermittent theta-burst stimulation (iTBS) and transcranial direct current stimulation (tDCS) combined with cognitive training in the treatment of post-stroke cognitive impairment (PSCI) requires further investigation. Methods: We randomly assigned 60 patients with PSCI to receive iTBS (n = 21), tDCS (n = 19), or cognitive training alone (n = 20). Cognitive function was evaluated by the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA), and the performance of activities of daily living (ADL) was assessed with the modified Barthel Index (MBI). Of these patients, 14 participated in the functional near-infrared spectroscopy (fNIRS) measurement. Results: After six weeks of treatment, cognitive function improved in all three groups of PSCI patients. Compared with patients receiving only cognitive training, the cognitive function of patients in the iTBS combined with cognitive training (p = 0.003) and tDCS combined with cognitive training groups (p = 0.006) showed greater improvement. The cognitive improvement from tDCS was related to the activation of the frontopolar cortex (FPC), while the improvement of cognition by iTBS was based on the activation of the stimulation site (the dorsolateral prefrontal cortex) and some distant regions. Conclusions: Both iTBS and tDCS in addition to cognitive training appear to improve cognitive function and quality of life of patients with PSCI, compared to cognitive training alone. tDCS improved cognitive function by improving the patient’s valuation, motivation, and decision-making substructures, while iTBS improved patients’ assessment and decision-making abilities, improving cognitive control and, ultimately, overall cognitive function.